Pemanfaatan Akun Instagram @lifeatinka sebagai Alat Publikasi untuk Meningkatkan Citra Perusahaan PT INKA (Persero) - Alhakim, Mahfudh Ghafur; Nurudin, Nurudin (Jurnal Audiens, 2025)
This study presents a strategic analysis of the use of the Instagram account @lifeatinka as a digital communication tool to enhance the corporate image of PT INKA (Persero). The main objective is to explain how the company employs digital communication strategies through the Instagram platform, supported by the graphic design application Canva and the video editing tool CapCut, to build and strengthen its corporate branding. The study focuses on audience interaction, visual effectiveness, and the role of social media in shaping public perception of the company.The research adopts a qualitative descriptive approach, with data collected through observation and documentation of the @lifeatinka Instagram account. The analysis evaluates the types of content, communication styles, and visual as well as audiovisual elements used in each post to identify PT INKA’s corporate branding strategy. The findings indicate that the strategic use of Instagram effectively fosters two-way interaction between the company and the public while creating a positive corporate image that reflects professionalism, openness, and innovation. Canva contributes to maintaining a consistent visual identity, while CapCut supports the creation of engaging and communicative video content. Overall, the integration of these elements makes PT INKA’s digital strategy effective in strengthening its corporate image and serves as a model of best practice in corporate communication within the digital transformation era.